Epigenetics and environment in breast cancer: New paradigms for anti-cancer therapies - Thakur, Chitra; Qiu, Yiran; Fu, Yao; Bi, Zhuoyue; Zhang, Wenxuan; Ji, Haoyan; Chen, Fei (Frontiers in Oncology, 2022)
Breast cancer remains the most frequently diagnosed cancer in women worldwide. Delayed presentation of the disease, late stage at diagnosis, limited therapeutic options, metastasis and relapse are the major factors contributing to breast cancer mortality. The development and progression of breast cancer is a complex and multi-step process that incorporates an accumulation of several genetic and epigenetic alterations. External environment factors and internal cellular microenvironmental cues influence the occurrence of these alterations that drives tumorigenesis. Here, we discuss state-of-the-art information on the epigenetics of breast cancer and how environmental risk factors orchestrates major epigenetic events, emphasizing the necessity for a multidisciplinary approach towards better understanding of the gene-environment interactions implicated in breast cancer. Since epigenetic modifications are reversible and are susceptible to extrinsic and intrinsic stimuli, they offer potential avenues that can be targeted for designing robust breast cancer therapies.